Infant Health, Cognitive Performance and Earnings: Evidence from Inception of the Welfare State in Sweden - Sonia R. Bhalotra; Martin Karlsson; Therese Nilsson; Nina Schwarz (Institute for the Study of Labor (IZA), 2016)
We estimate impacts of exposure to an infant health intervention trialled in Sweden in the early 1930s using purposively digitised birth registers linked to school catalogues, census files and tax records to generate longitudinal microdata that track individuals through five stages of the life-course, from birth to age 71. This allows us to measure impacts on childhood health and cognitive skills at ages 7 and 10, educational and occupational choice at age 16-20, employment, earnings and occupation at age 36-40, and pension income at age 71. Leveraging quasi-random variation in eligibility by birth date and birth parish, we estimate that an additional year of exposure was associated with improved reading and writing skills in primary school, and increased enrolment in university and apprenticeship in late adolescence. These changes are larger and more robust for men, but we find increases in secondary school completion which are unique to women. In the longer run, we find very substantial increases in employment (especially in the public sector) and income among women, alongside absolutely no impacts among men. We suggest that this may be, at least in part, because these cohorts were exposed to a massive expansion of the Swedish welfare state, which created more jobs for women than for men.
Keywords: I15; I18; H41; 330; infant health; early life interventions; cognitive skills; education; earnings; occupational choice; programme evaluation; Sweden